(untitled) (Docentes 2.0 Journal, 2020)
Image Pedagogy (IP) is proposed as the most suitable way to promote meaningful learning within the classroom. The elements that underpinned this proposal arise from field research, of a descriptive nature. The participating group was made up of 5 teachers assigned to the Chair of Environmental Education (EA) of the Pedagogical Institute of Caracas (IPC). The data collection techniques and tools were: a) the survey for diagnosis and feasibility accompanied by the questionnaire and (b) the observation and the questionnaire for the validation of the strategies designed. The results were analyzed from descriptive statistics, concluding that: (a)Teachers intuitively use IP but do not have a theoretical foundation that allows its effective application and (b) the proposal meets the pedagogical criteria for its future application, which is why its implementation is recommended by teachers who aspire to respond to the demands of today’s society.